Investigation on the clinical use and research hotspot of Lingnan native medicinal materials - Yingchao LIANG; Yanzhu ZHONG; Siyi LI; Meitang HE; Yulu FENG; Zhanyao LIANG (KeAi Communications Co., Ltd., 2020)
[Abstract]: Lingnan native medicinal materials refer to the drugs which are widely used by the people of Lingnan, China and nearby regions, have definite medicinal effects, and are produced locally. Based on the data provided by Guangzhou Kangmei Smart Pharmacy, the authors of this study cross-analyzed the actual amount of use and the research hotspot of the drugs from the collected data and found and studied the drugs with high research value. The purpose of this study was to clarify the relationship between the research hotspot and the actual amount of use of the drugs, reveal the deviation between the using status of Lingnan native medicinal materials and the experience of famous Traditional Chinese Medicine (TCM) doctors, and to provide supporting data and explore possible directions for the development and utilization of Lingnan native medicinal materials.